Black Mike : a Western duo - Overholser, Wayne D. 1906-1996 (Thorndike, Maine Center Point Large Print, 2015)
"Two Western stories about young men who return to their home towns and are faced with difficult decisions that will require them to use their guns"--
Gun in his hand -- Black Mike.
104908
Keywords: Large type books; Sheriff; Cattlemen; Father/Son; Western stories